Patients Who Fainted Whilst Giving a Blood Sample in the Blood Collectıon Unit and a Stress Mediator: Cortisol - Şenol Arslan; Mevlana Ömeroğlu (Genel Tıp Dergisi)
OBJECTIVE: Cortisol is a glucocorticoid and can be used as a stress mediator in association with adrenal insufficiency. A diagnosis of adrenal insufficiency is made when the episodically released cortisol levels are below 3 mcg/dl by making a single measurement at any time of the day. We aimed to determine the presence of underlying adrenal insufficiency by measuring cortisol levels in patients brought to the emergency room by the hospital code blue team that firstly performed their critical care, who fainted whilst giving blood samples in the blood collection unit. MATERIAL AND METHODS: Observational, prospective study; It consists of 28 patients brought to emergency department by Code Blue Team between 2017 and 2020. After physical examination and electrocardiogram(ECG) evaluation, samples were taken for complete blood count, biochemical parameters, venous blood gas, cardiac biomarkers and cortisol measurement. Obtained results were analyzed with SPSS 22. RESULTS: The lowest cortisol level was 9 mcg/dL, and the highest cortisol level was 40,4 mcg/dL. Cortisol levels were higher in women than men. But T-test analysis revealed that gender is not a determining factor in cortisol levels (p=0,26). The correlation between blood collection time and cortisol values was calculated close to zero (r2=0.09). The patient diagnosed with adrenal insufficiency with a single measurement was not defined in the study population. CONCLUSIONS: Patients with acute adrenal insufficiency may come to the emergency department with orthostatic hypotension, agitation, syncope, abdominal pain and fever, and may result in death if left untreated (1). Although emotional stress is 20% among the precipitating factors of adrenal crisis, no significant relationship was found between stress and cortisol in our study (2). The limitations of our study are that it can only be carried out during working hours, and advanced diagnostic tests can not be performed in the emergency room.